Focal mechanism solutions and its tectonic significance in the trench of the eastern South China Sea - 朱俊江 丘学林 詹文欢 徐辉龙 孙龙涛 (Acta seismologica sinica, 2005)
According to the activity of earthquakes and volcanoes along the Manila trench and its adjacent region, combined with analysis of focal mechanism solutions and geophysics data, the Manila trench is still being downward subduction in the depth of 200 km. Deep earthquakes mainly concentrate between 12°N and 14°N, the concentrated region is divided into different sections, and the focal depth is gradually deep from the north to the south. From the focal mechanism solution data, the maximum principal stress direction (P axis) varies from the northern region of Philippine fault to the southern region of the fault. In the north P axes directions are mainly NW, however in the south there is the complex displaying and P axes have NW, NE and approximately NS directions. These results show the characteristics of press-thrust in the northern region of the Philippine fault and the clockwise rotation in the southern region of the fault. The stress caused by the Philippine plate, which moved upon the South China Sea sub-plate, is adjusted by the oblique subduction of the Manila trench, the sinistral strike-slip of the Philippine fault and the sinistral strike-slip of the Mindoro fault.[PUBLICATION ABSTRACT]